Hepatic epithelioid hemangioendothelioma: how fast does it grow and which findings could have prevented diagnostic delay?-a case report - Ribeiro, Michele Costa de Oliveira [UNESP]; Lemos, Juliana Viana Baiao; Moraes, Marcelo Padovani de Toledo [UNESP]; Oliver, Felipe Aguera [UNESP]; Alvarez, Matheus; Silva, Giovanni Faria [UNESP]; Qi, Xingshun; Romeiro, Fernando Gomes [UNESP] (Ame Publishing Company, 2022)
Background: Hepatic epithelioid hemangioendothelioma (HEHE) is a rare neoplastic disease of varied presentation and unspecific radiological signs in the early stages. The diagnostic delay can lead to metastatic disease, thus increasing the tumor burden and reducing the treatment options. HEHE is usually deemed a slow-growing tumor, but its speed of growth is poorly reported and still unknown.Case Description: In this case report, we documented a HEHE diagnosed in a young woman who had complaints of abdominal pain, weight loss and bloating for a long time. The typical findings observed in histological studies were not promptly recognized in the histological analyzes, even after two laparoscopicguided liver biopsies, delaying the diagnosis until extrahepatic tumor spreading. Findings observed in computed tomography, magnetic resonance imaging and histological studies are presented. The coalescence of nodules and the rising of giant masses, occupying large parts of the liver in a specific time span, were registered and quantified. As opposed to prior reports, the results show that hepatic HEHE can grow rapidly, reinforcing the need of early diagnosis, thus avoiding the complications presented herein.Conclusions: The findings observed via radiological and histological imaging that could have avoided the diagnosis delay are depicted and discussed, showing that HEHE can rise faster than previously documented.
Keywords: Liver cancer; extrahepatic metastasis; imaging; liver neoplasms; case report